Structural-phase transformations in near-surface layers of alumina-zirconium ceramics induced by low-energy high-current electron beams - Surzhikov A. P. Anatoly Petrovich; Frangulyan T. S.; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Koval N. N. Nikolay Nikolaevich (2009, 2009)
Title screen